2015
DOI: 10.1177/1687814015590312
|View full text |Cite
|
Sign up to set email alerts
|

Bilinear load-deflection model of fiber-reinforced polymer–concrete composite beam with interface slip

Abstract: The design of fiber-reinforced polymer-concrete hybrid beam is usually governed by deformation. Due to the rigidity degradation caused by fiber-reinforced polymer-concrete slip, the load-slip and load-deflection curves demonstrate a bilinear characteristic. The originality of this article is to propose a bilinear analytical model and to determine two dominant parameters in this model, namely, initial bond stress and slip modulus of the interconnection. This model consists of two distinct linear stages. In Stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…The research of Yuan et al (Yuan and Hadi, 2017) showed that with the ignorance of the bond-slip of composite beams, the stiffness and ultimate load of the structure will be overestimated. Wang (Wang et al, 2015) highlights the debonding mechanism of the GFRP concrete composite beams theoretically, which is verified by the tests. Furthermore, Umberto (Umberto et al, 2021) used the cohesive model to simulate the bond-slip of FRP-strengthened concrete beams, and the results were in good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 63%
“…The research of Yuan et al (Yuan and Hadi, 2017) showed that with the ignorance of the bond-slip of composite beams, the stiffness and ultimate load of the structure will be overestimated. Wang (Wang et al, 2015) highlights the debonding mechanism of the GFRP concrete composite beams theoretically, which is verified by the tests. Furthermore, Umberto (Umberto et al, 2021) used the cohesive model to simulate the bond-slip of FRP-strengthened concrete beams, and the results were in good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 63%
“…4. An equation for deflection of a beam can be found by direct integration of curvature using Euler-Bernoulli beam theory (Garcez & Silva Filho, 2009;Wang, 2015). The bi-linearity of the (4) δ max,el = ϕ 24 3L 2 − 4a 2 , moment-curvature relation of strain-hardening fiber reinforced cementitious material beam under monotonic loading was verified by Soranakom and Mobasher (2007).…”
Section: Analytical Calculation Of Deflectionmentioning
confidence: 92%
“…Closed-form analytical solutions for calculating deflection of beams and slabs under various loadings and assuming bi-linear moment-curvature relationship of cross-section were developed in Wang (2015). By means of a parametrized constitutive law of UHPFRC (Soranakom & Mobasher, 2007), bending moment-deflection curves were calculated, reflecting well the structural response of a beam.…”
Section: Literature Review On Modelling Of Uhpfrcmentioning
confidence: 99%
“…4,13 The subsequent peeling of the FRP degrades the load-bearing capacity of the member, which then fails to reach its expected design value. 14 Therefore, effective monitoring and inspection of the interfacial bond between concrete and FRP is a prerequisite for ensuring the desired strengthening effect.…”
Section: Introductionmentioning
confidence: 99%